Gangs of New York [videorecording (DVD)] - Scorsese, Martin; DiCaprio, Leonardo; Day-Lewis, Daniel; Diaz, Cameron (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2003)
In 1846, waves of Irish immigrants poured into the New York neighborhood of Five Points. "Billy the Butcher" bands his fellow "Native Americans" into a gang to take on the Irish gang "The Dead Rabbits," organized by Priest Vallon. After an bloody clash Vallon is dead and his son ends up in a brutal reform school. In 1862, that boy returns to seek vengeance against the man that killed his father.